Harmonization of Artificial Intelligence (Ai) in Indonesia: Exploration of Technology And Ethics in Islam - Mufidah, Mufidah; Hartiwiningsih, Hartiwiningsih; Isharyanto, Isharyanto (Universitas Muhammadiyah Surakarta, 2024)
Indonesia is one of the countries that agrees that AI (Artificial Intelligence) has a positive influence on human life.The presence of AI (Artificial Intelligence) as a form of technological progress simultaneously also raises various ethical challenges such as issues of privacy, justice, uneven social impacts and even ignoring the decline in moral values. Therefore, in this article we will explore how AI (Artificial Intelligence) can influence human dignity and freedom, then also how technology can influence human relationships with the universe and its creator which is developed through a regulatory framework that takes into account religious ethical values ​​in the Islamic view so that they have a guide to the use of AI (Artificial Intelligence). This research is normative legal research, the author uses three approaches which include: (a) philosophical approach, (b) statutory approach, (c) conceptual approach. . The primary data for this research are: (1) Primary legal materials consisting of: the 1945 Constitution of the Republic of Indonesia, ITE Law no. 11 of 2008 along with government regulation no. 71 of 2019 concerning PSTE as well as the Koran, Hadith and Ijtihad (2) Secondary legal materials consisting of: books, legal journals, expert opinions. The results of this research show two things, namely: (1) The blurring of privacy protection due to the application of AI systems in various aspects of life so that AI artificial intelligence accompanied by technological advances needs to be evaluated. (2) There must also be someone who ensures the security of the system, and establishes an appropriate responsibility framework. Indonesia adalah salah satu negara yang percaya bahwa AI (artificial intelligence/kecerdasan buatan) dapat meningkatkan kehidupan manusia. Sebagai salah satu bentuk kemajuan teknologi, AI memunculkan dilema etika seperti privasi, keadilan, dampak sosial yang tidak merata, dan mengabaikan kemerosotan moral. Artikel ini akan mengkaji bagaimana AI dapat mempengaruhi martabat dan kebebasan manusia, serta bagaimana teknologi dapat mempengaruhi hubungan manusia dengan alam semesta dan Tuhan, yang dikembangkan melalui kerangka peraturan yang mempertimbangkan nilai-nilai etika agama Islam untuk memandu penggunaan AI. Penelitian ini merupakan penelitian hukum normatif, penulis menggunakan tiga pendekatan yang meliputi: (a) pendekatan filosofis, (b) pendekatan perundang-undangan, (c) pendekatan konseptual. Data dalam, penelitian ini terdiri: (1) Bahan hukum primer yang terdiri dari: Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, Undang-Undang ITE No. 11 Tahun 2008 beserta Peraturan Pemerintah No. 71 Tahun 2019 tentang PSTE serta Al-Qur'an, Hadist dan Ijtihad (2) Bahan hukum sekunder yang terdiri dari: buku-buku, jurnal-jurnal hukum, pendapat para ahli. Hasil penelitian ini menunjukkan bahwa semakin kaburnya perlindungan privasi akibat penggunaan sistem AI di berbagai sektor kehidupan mengharuskan adanya tinjauan ulang terhadap AI, dan kemajuan teknologi.